Gambaran Pending Klaim BPJS Rawat Inap di Rumah Sakit Umum Daerah Kebayoran Lama - Ahmad Rozikin; Nanda Aula Rumana; Putery Fannya; Muhammad Fuad Iqbal (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Pending claims from BPJS Kesehatan remain a major issue in hospital financial management, particularly in inpatient services. Returned or pending claims may disrupt hospital cash flow and affect the continuity of healthcare services. This study aimed to determine the percentage and causes of returned BPJS inpatient claims that resulted in pending status at Kebayoran Lama Regional General Hospital (RSUD Kebayoran Lama). This study employed a descriptive quantitative design with a cross-sectional approach. The study population consisted of all BPJS inpatient claim files that experienced pending status from April 2025 to August 2025. Data were collected through document observation of claim files, and analyzed using descriptive statistics to determine the percentage of pending claims based on their causes. The results showed that out of 950 submitted claims, 246 claims (25.89%) were pending. The main contributing factor was medical issues (63%), followed by administrative factors (19.91%) and coding factors (17.07%). Medical factors included incomplete medical discharge summaries and insufficient supporting diagnostic examinations. These findings indicate a gap between BPJS claim requirements and the completeness of medical documentation in the hospital. In conclusion, this study highlights the need to improve the completeness of medical records, strengthen coordination among service units, and enhance the accuracy of coding officers in order to reduce the rate of pending BPJS claims.